Misconception about Halal Certification Placement on Non-Food Commodities: State Coercion over the Territory of Ijtihad - Hamid, Abdul; Fakhrina, Agus; Aziz, Fathul Aminudin; Mursid, Mansur Chadi (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
The obligation of halal certification for commodity products has created many dilemmas, one of which is the placement of the halal label on non-consumer goods. This is evidenced by the use of halal labels on several animal food products and non-food products. Even halal certification is also placed in the service sector, which is included in the supply chain management activities category. This study examines the government mandate for halal certification of commodity products and highlights the resulting public misunderstandings about the application of halal labels. Data were gathered from various online platforms, including news outlets, pet food websites, and sites unrelated to consumer goods that discuss halal certification. These sources were examined using descriptive analysis. The findings reveal that, on the one hand, the government helps consumers choose halal products; on the other, making the State the sole authority on what's halal and what's haram has confused halal labels and imposed legal pressure on matters that rightly belong in the domain of ijtihad. The mandatory halal certification imposes the formalism of religious language, leading people to feel that their economic activities are being dictated in the name of the common good, while disregarding alternative perspectives in assessing a product's halal or haram status. This finding underscores the need for additional follow-up measures to determine the extent of the benefits achievable through this mandatory halal certification requirement.